Recent Developments in the Experimental Elicitation of Time Preference - Stephen L. Cheung (Institute for the Study of Labor (IZA), 2016)
This methodological survey reviews recent developments in the design of experiments to elicit individuals' time preferences, with a focus on the measurement or control for potentially non-linear utility. While the objective of a time preference experiment is usually to estimate parameters of a discount function, assumptions concerning the nature of utility may have an important influence upon these estimates. The survey classifies experiment designs on two dimensions: whether they assume an equivalence between utility under risk and over time, and whether they result in an estimate of the curvature of utility.
Keywords: C91; D03; D90; 330; instantaneous utility; discounted utility; time preference; choice list